Menerima Hasil Transaksi Seksual Bagi Pelacur dalam Perspektif Hadis Ahkam Ekonomi - Haddad Ulum Harahap (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This study discusses the prohibition of receiving proceeds from sexual transactions in prostitution practices based on the perspective of the economic aḥkām hadith. Prostitution, as a form of sexual deviation and adultery, is not only seen as damaging to moral and social order, but also contrary to the principles of sharia economics which emphasize the permissibility and blessing of income sources. The focus of the study is to analyze authentic hadiths, especially those narrated by al-Bukhārī, Muslim, al-Bayhaqī, and Ibn Mājah, which explicitly prohibit mahr al-baghī (prostitutes' wages) as a form of illicit wealth. Using a qualitative method based on literature studies through the analysis of sanad, matan, and istinbāṭ law, this study finds that all forms of receiving wealth from prostitution activities are illegitimate according to sharia because they contradict the maqāṣid al-shari'ah, especially the protection of honor and offspring. The findings of this study confirm that income from prostitution cannot be considered halal (lawful) assets, cannot be used as an object of transaction, and has no economic blessings. Furthermore, the study identifies several challenges in the implementation of Islamic law regarding prostitution, such as weak legal socialization, lack of public understanding, and minimal social and economic policy intervention. This research contributes to strengthening the study of Islamic economics and provides a normative foundation for developing policies to combat prostitution based on Islamic values.